Determination of aloesin in rat plasma using a column-switching high-performance liquid chromatographic assay - Baek, M; Jeong, JH; Kim, DH (ELSEVIER SCIENCE BV, 2001)
A column-switching high-performance liquid chromatography (HPLC) method for the determination of aloesin in rat plasma using column-switching and ultraviolet (UV) absorbance detection is described. Plasma was directly injected onto the HPLC system consisting of a clean-up column, a concentrating column, and an analytical column, which were connected with a six-port switching valve. The determination of aloesin was accurate and repeatable, with a limit of quantitation of 10 ng/ml in plasma. The standard calibration curve for aloesin was linear (r=0.998) over the concentration range of 10-1000 ng/ml in rat plasma. The intra- and inter-day assay variabilities of aloesin ranged from 1.0 to 4.7% and 1.1 to 8.8%, respectively. This highly sensitive and simple method has been successfully applied to a pharmacokinetic study after oral administration of aloesin to rats. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: ARBORESCENS MILLER